2010
DOI: 10.1111/j.1521-0391.2010.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differences in Substance Use among Rural and Urban Pregnant Women

Abstract: Substance use during pregnancy is a major public health concern. This study examined differences in substance use among pregnant women from rural and urban areas. Participants were 114 pregnant women entering a hospital-based inpatient detoxification unit primarily for Opiate Dependence who voluntarily agreed to a face-to-face interview. Substance use measures were based on the Addiction Severity Index gathering information about lifetime, past 12 months, and 30 days prior to admission. Rural pregnant women ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 31 publications
0
42
2
Order By: Relevance
“…Martin and colleagues (2014) found that despite a relatively constant rate of admissions of pregnant women to substance use disorder treatment settings from 1992 to 2012, the prevalence of pregnant woman seeking treatment specifically for prescription opioid abuse has increased 14-fold. Prescription drug abuse may be more prevalent among rural pregnant women (Shannon, Havens, & Hays, 2010). Given the importance of treatment for pregnant women to both the health of the mother and of the developing fetus, more research with this subgroup is needed.…”
Section: Epidemiology Of Prescription Drug Abusementioning
confidence: 99%
“…Martin and colleagues (2014) found that despite a relatively constant rate of admissions of pregnant women to substance use disorder treatment settings from 1992 to 2012, the prevalence of pregnant woman seeking treatment specifically for prescription opioid abuse has increased 14-fold. Prescription drug abuse may be more prevalent among rural pregnant women (Shannon, Havens, & Hays, 2010). Given the importance of treatment for pregnant women to both the health of the mother and of the developing fetus, more research with this subgroup is needed.…”
Section: Epidemiology Of Prescription Drug Abusementioning
confidence: 99%
“…In addition studies have indicated that pregnant patients from rural areas have higher rates of drug dependence compared to their urban counterparts. A recent study by Shannon et al (2010) with 114 pregnant patients entering care for inpatient detoxification for opiate dependence revealed that rural women had higher rates of illicit opiate use (nonprescription), illicit sedative or benzodiazepine use, and injection drug use in the 30 days prior to admission for detoxification when compared to their urban counterparts admitted for opiate dependence. Shannon et al found in their study that it was critically important to understand the “context of demographic, geographic, social and economic conditions of the region” (Appalachia/Kentucky) to treat substance abuse effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that pregnant patients from rural areas have higher rates of drug dependence compared to their urban counterparts (Shannon, Havens, & Hays, 2010). Charleston Area Medical Center (CAMC), West Virginia's only free-standing Women and Children's Hospital, serves both urban and rural communities with 23.3% of obstetrical patients from rural counties.…”
mentioning
confidence: 99%
“…9 Given these differing definitions, the descriptions of pregnant women with opioid dependence who reside in these areas vary widely in terms of socioeconomic status, ethnic diversity and proximity to urban resources. 10 Heroin is the most commonly reported opioid used by pregnant women living in rural and remote communities, 2,10,11 but the nonmedical use of prescription opioids is increasing. 10,11 Regardless of the opioid in use, treatment strategies for pregnant women in these communities primarily involve methadone maintenance.…”
mentioning
confidence: 99%
“…10 Heroin is the most commonly reported opioid used by pregnant women living in rural and remote communities, 2,10,11 but the nonmedical use of prescription opioids is increasing. 10,11 Regardless of the opioid in use, treatment strategies for pregnant women in these communities primarily involve methadone maintenance. 2,3 What is the recommended treatment for opioid dependence during pregnancy?…”
mentioning
confidence: 99%